Tissue-Engineered Breast Reconstruction with Brava-Assisted Fat Grafting: A 7-Year, 488-Patient, Multicenter Experience. Issue 3 (March 2015) - Khouri, Roger K.; Rigotti, Gino; Khouri, Roger K.; Cardoso, Eufemiano; Marchi, Alessandra; Rotemberg, Silvia C.; Baker, Thomas J.; Biggs, Thomas M.
Abstract : Background: The ability of autologous fat transfer to reconstruct an entire breast is not established. The authors harnessed the regenerative capabilities of external expansion and autologous fat transfer to completely reconstruct breasts. Methods: The authors performed 1877 Brava plus autologous fat transfer procedures on 616 breasts in 488 women to reconstruct 99 lumpectomies, 87 immediate breast reconstructions, and 430 delayed total breast reconstructions. After 2 to 4 weeks of Brava expansion, which increased volume by 100 to 300 percent, the authors diffusely grafted the breasts with 100 to 400 ml (225 ml average) of 15 g –sedimented, manually harvested lipoaspirate. The procedure was repeated every 8 to 14 weeks until completion. The authors compared costs of this reconstruction with established deep inferior epigastric artery perforator/transverse rectus abdominis musculocutaneous flaps and implant procedures. Results: Follow-up ranged from 6 months to 7 years (mean, 2.5 years), with 0.5 percent locoregional recurrence. Four hundred twenty-seven women completed the reconstruction, whereas 12.5 percent dropped out (2.5 percent medical, 10 percent personal reasons). Completion required 2.7 procedures for nonirradiated and 4.8 procedures for irradiated mastectomies. Patients recovered soft, natural appearing breasts with nearly normal sensation. Complications included five pneumothoraces and 20 ulcerative infections. Radiographically recognized benign palpable masses were observed in 12 percent of nonirradiated and 37 percent of irradiated breasts. The cost of Brava plus autologous fat transfer is 47 percent and 66 percent that of current reconstruction alternatives. Conclusion: Brava plus autologous fat transfer is a minimally invasive, incisionless, safe, economic, and effective alternative for breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.